Bullyng: Acoso y violencia escolar - Balarezo López, Gunther (2015)
A literature review of the issues related to “bullyng” was performed. To this end, various publications are analyzed and the most relevant aspects are summarized. This behavior is more common than what it thinks and has serious consequences for victims, affecting their daily and personal lifes, being able in some cases to present suicide. As such, families and school authorities are called upon to identify cases of violence and control this type of behavior.